Physician engagement in regularly scheduled rounds - Bass, Adam; Armson, Heather; McLaughlin, Kevin; Lockyer, Jocelyn (Canadian Medical Education Journal, 2020)
Background: Physician participation in regularly scheduled series (RSS), also known as grand rounds, was explored with a particular focus on physician perceptions about the elements that affected their engagement in RSS and the unanticipated benefits to RSS. Methods: A qualitative study using semi-structured interviews and thematic analysis examined physicians’ perception of their knowledge and educational needs and the factors that contributed to engagement in their local hospital RSS. Results: Physician engagement in RSS was affected by four major themes: Features that Affect the RSS’ Quality; Collegial Interactions; Perceived Outcomes of RSS; and Barriers to participation in RSS. Features that Affect RSS’ Quality were specific modifiable features that impacted the perceived quality of the RSS. Collegial Interactions were interactions that occurred between colleagues directly or indirectly as a result of attending RSS. Outcomes of RSS were specific outcome measures used in RSS sessions. Barriers were seen as reasons why physicians were unwilling or unable to participate in RSS. All of the elements identified within the four themes contributed to the development of physician engagement. Physicians also identified changes directly and indirectly due to RSS. Discussion: Specific features of RSS result in enhanced physician engagement. There are benefits that may not be accounted for in continuing medical education (CME) outcome study designs